Ergonomic Risk Factors in University-Level Teachers in Sonora, Mexico: Towards a Sustainable Environment. - Duarte, Nancy Esmeralda Sánchez; Valdéz, Hugo César De La Torre; Romero, Daniel Morales; Hernandez, Mabeth Burgos; Acosta, Judith Valeria Martínez; Murrieta, Maribel Pallanez (Journal of Health Scope, 2025)
Background: A sustainable environment plays a crucial role in mitigating musculoskeletal disorders, visual fatigue, stress, and exhaustion. Consequently, it enhances productivity and promotes greater work efficiency, contributing to workers' overall well-being. While ergonomic risk studies are widely documented in the literature, most focus on the industrial sector, with limited ergonomic assessments available in the educational sector. Objectives: Evaluate ergonomic risk factors among teachers to foster a sustainable environment. Methods: A quantitative study employed an observational, cross-sectional design to measure the ergonomic risk between April and June 2023. The Rapid Office Strain Assessment (ROSA) method was employed using the ERGONIZA software to assess full-time professors (FTP) in a university in Sonora, Mexico, through a statistically representative survey applied with 92% reliability and a maximum allowed error (α) of 0.08. Results: The results indicated that out of 158 FTP, 48.7% are at very high risk, 23.1% at high risk, and 28.2% at improvable risk. Conclusions: A sustainable environment contributes to improving worker well-being, combating absenteeism and medical costs, increasing productivity, and, therefore, leading to greater work efficiency. The ROSA method does not consider some parameters like environmental elements (lighting and temperature).